Heat Transfer Augmentation of a Car Radiator using Nanofluids - M., Adnan Hussein; R. A., Bakar; K., Kadirgama; Sharma, K. V. (Springer Berlin Heidelberg, 2014)
The car radiator heat transfer enhancement by using TiO2 and SiO2 nanoparticles dispersed in water as a base fluid was studied experimentally. The test rig is setup as a car radiator with tubes and container. The range of Reynolds number and volume fraction are (250–1,750) and (1.0–2.5 %) respectively. Results showed that the heat transfer increases with increasing of nanofluid volume fraction. The experimental data is agreed with other investigator.